Analisis Harga Pokok Produksi Dengan Metode Variable Costing (Studi Kasus Di Cv. Sumber Mulyo. Klaten) - Kustanto, Kustanto, Ahmad Kholid Al Ghofari, S.T., M.T, Ratnanto Fitriadi, ST., MT (2015)
In this era of globalization, industries in Indonesia need to be aware that must constantly improve its performance by improving the system of production costs. Besides for profit but also as a determinant for maintaining the viability of the business. CV. Source Mulyo is a company engaged in furniture such as cabinets, tables, chairs. The purpose of this study is to calculate the cost of the product with variable costing method to obtain the right product cost and selling prices are optimal. After calculation and analysis obtained by the method of variable costing the cost of production per unit amounted to USD 2.55716 million adjuvant Rp 358 500 cost of raw materials can be Rp 1.935 million and the cost of electric power amounted to USD 17 660, labor costs Rp 176,000 with profit gained 40% to Rp 1,022,864 and Rp 3,580,024 in sales of 1-month period to come. CV. Mulyo sources must be improved and in setting the price of the company should be more careful, so as to produce the optimal profit and remain competitive national market.